Long-term Trends in Singleton Preterm Birth in South Australia From 1986 to 2014. Issue 1 (January 2018) - Verburg, Petra E.; Dekker, Gus A.; Venugopal, Kamalesh; Scheil, Wendy; Erwich, Jan Jaap H. M.; Mol, Ben W.; Roberts, Claire T.
Abstract : OBJECTIVE: To describe long-term trends in the prevalence of preterm birth and rates of preterm birth in singleton pregnancies complicated by hypertensive disorders of pregnancy, small for gestational age (SGA), and preterm prelabor rupture of membranes (PROM) in South Australia. METHODS: We conducted a retrospective population study including all singleton live births in the state of South Australia from 1986 to 2014. Long-term trends for preterm birth, hypertensive disorders of pregnancy, SGA, preterm PROM as well as stillbirth were assessed using joinpoint regression analyses. Trends in maternal age, body mass index (BMI), ethnic diversity, parity, and smoking over time were also assessed. RESULTS: From 1986 to 2014, with a total of 539, 234 singleton births, the overall preterm birth rates increased from 5.1% to 7.1% ( P <.001) and for iatrogenic preterm birth increased from 1.6% to 3.2% ( P <.001). The incidence of hypertensive disorders of pregnancy decreased from 8.7% to 7.2%. Among pregnancies complicated by hypertensive disorders of pregnancy, the proportion of preterm birth increased (10.4–17.5%, P <.001). The incidence of SGA decreased from 11.1% to 8.0%. Among pregnancies complicated by SGA, the proportion of preterm birth increased (2.9–5.4%, P <.001). The incidence of preterm PROM increased from 1.4% to 2.2%. Among pregnancies complicated by preterm PROM, the proportion of preterm birth remained stable. Preterm stillbirth rates declined (4.23–2.32%, P <.001). Maternal age, BMI, and ethnic diversity have all increased since 1986, whereas maternal smoking has decreased. CONCLUSION: In South Australia, the preterm birth rate among singletons increased from 1986 to 2014 by 40%, with iatrogenic preterm birth being responsible for 80% of this increase. Incidence of hypertensive disorders of pregnancy and SGA declined. Among pregnancies complicated by hypertensive disorders of pregnancy and SGA, the proportions of preterm birth increased, indicating earlier interventions in these women. The diagnosis of preterm PROM increased from 1% to 2%, and greater than 80% of preterm PROM was associated with preterm birth after 1990. Increasing iatrogenic delivery may be attributable, in part, to changing maternal phenotype and to altered clinicians' behavior. However, improvements in fetal surveillance, particularly ultrasonography, and advanced neonatal care may underpin perinatal clinical decision-making and the likelihood of iatrogenic birth. Abstract : In South Australia, from 1986 to 2014, the preterm birth rate among singleton births increased from 5% to 7%, mostly as a result of increased iatrogenic delivery.